Research on the Relationship Between Green Energy Use, Carbon Emissions and Economic Growth in Henan Province - Wang, Ya-li (Frontiers in Energy Research, 2021)
This article takes Henan Province as the research object and analyzes the relationship between the green energy use, carbon emissions and economic growth in Henan Province by constructing a VAR model.The results show that :(1) There is a long-term equilibrium relationship between the green energy use, carbon emissions and economic growth in Henan Province. The green energy use can simultaneously promote the reduction of carbon dioxide emissions and sustainable growth of economy;(2)The article examines the "creative" effect and "destructive" effect of green energy use on economic structure in Henan Province, and the "creative" effect is greater than the "destructive" effect, so, the green energy use can help Henan Province to achieve green and low-carbon economic growth; (3) Carbon dioxide emission and economic growth are the important factors affecting the green use of energy in Henan Province. Recently, the call of national carbon emission reduction and the pressure of economic development transition have induced Henan Province to change to a clean and green use of energy to some extent; (4) The contribution rate of green energy use to economic growth shows an inverted U-shaped trend, which increases first and then decreases. Carbon emission has influence on both green energy use and economic growth to a certain degree. Finally, targeted recommendations are presented to promote the green energy use and ensure the coordinated and sustainable development of economy and environment of Henan Province.